The Influence of Financial Literacy, Cognitive Bias and Emotional Bias on Financial Sector Investment Decisions in West Kalimantan with Risk Preference as an Intervening Variable - Listianingsih, Siti Nur Azizul (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
The purpose of this study was to test and analyze the effect of Financial Literacy, Cognitive Bias and Emotional Bias on Investment Decisions with Risk Preference as an intervening variabel. This research uses causal research. The hypothesis tested is the effect of the variabels of Financial Literacy, Cognitive Bias and Emotional Bias on Risk Preference, the variabels of Financial Literacy, Cognitive Bias and Emotional Bias on Investment Decisions. The sample used in this study amounted to 327 samples from people in West Kalimantan selected using purposive sampling technique. Analysis techniques in processing and analyzing data using Eviews 13 software with multiple linear regression testing and Sobel test. The results of this study indicate that in Equation I, Financial Literacy and Cognitive Bias partially do not have a positive influence on Risk Preference. While the Emotional Bias variabel partially has an influence on Risk Preference.